Incorporating sense of place into the management of social-ecological systems: The researchers' perspectives. - Joe Duggan; Sarah Clement; Christopher Cvitanovic; Ingrid van Putten (PLoS ONE)
As the world around us changes, so too do the bonds that people have with their environment. These environmental bonds, or Senses of Place (SoP), are a key component of social-ecological systems (SESs). SoP has social, psychological and economic value, it impacts how people use and behave in an environment and how they respond to changes such as those caused by anthropogenic pressures. Despite this connection, the consideration and application of SoP in the management of SESs remains relatively under explored. This study takes the first step in addressing that gap by investigating the perceptions of researchers in the field. We achieve this by interviewing SoP researchers from around the globe to elucidate whether they see SoP as valuable for the management of SES. We also identify their perspectives on the barriers to, and enablers of, incorporating SoP into policy and management. Results show while researchers do see the value in incorporating SoP into policy, there are a range of barriers that impact this, most notably, the intangible nature of the phenomena and shortcomings of current governance systems. Results also identify a range of enablers that could improve the incorporation of SoP into policy-particularly through improved engagement and communication between stakeholders. These findings represent a first step in the formal inclusion of this social value into the management of SES.